Contribution of Sex and Autoantibodies to Microangiopathy Assessed by Nailfold Videocapillaroscopy in Systemic Sclerosis: A Systematic Review of the Literature. Issue 5 (3rd April 2021) - van Leeuwen, Nina M.; Ciaffi, Jacopo; Schoones, Jan W.; Huizinga, Tom W. J.; de Vries‐Bouwstra, Jeska K.
Abstract : Objective: Microangiopathy and dysregulation of the immune system play important roles in the pathogenesis of systemic sclerosis (SSc). Factors that trigger vascular injury in SSc have not been elucidated so far. We undertook this study to evaluate whether sex or expression of specific antinuclear autoantibodies might associate with the degree of microangiopathy through performance of a systematic review that summarizes what is known about these associations. Methods: A standardized search of PubMed, Embase, Web of Science, and the Cochrane Library were performed to identify studies that described autoantibodies in SSc patients and microangiopathy and, for the second search, those that described sex and microangiopathy. Results: We included 11 studies that described the relationship between SSc‐specific autoantibodies and microangiopathy and 6 studies that reported on the association between sex and microangiopathy. Contradictory results were found on the association between SSc‐specific autoantibodies and microangiopathy, and no association was found between sex and microangiopathy based on the current literature. Conclusion: Based on this review of the literature, we can conclude that sex does not seem to influence degree of microangiopathy in SSc, while results on association between SSc‐specific autoantibodies and degree of microangiopathy were inconclusive.